Lullington Church
The point arch appears here in the gable of a doorway to another country church, in a rare combination of Romanesque arch, carved tympanum, niche, and gable. The doorway, carved at Caen in Normandy, was shipped from France, but the figure of Christ has much of the same quality as that of Malmesbury, not so far away.